Ectopic Posterior Pituitary, Polydactyly, Midfacial Hypoplasia and Multiple Pituitary Hormone Deficiency due to a Novel Heterozygous IVS11-2A>C(c.1957-2A>C) Mutation in the GLI2 Gene - Meliha Demiral; Hüseyin Demirbilek; Edip Unal; Ceren Damla Durmaz; Serdar Ceylaner; Mehmet Nuri Özbek (Galenos Yayincilik, 2020)
A novel heterozygous IVS11-2A>C(c.1957-2A>C) mutation in the GLI2 gene is reported. There was an extremely distinct phenotypical expression in two siblings and their father. The index case was a boy who developed cholestasis and hypoglycaemia in the neonatal period. He had bilateral postaxial polydactyly, mid-facial hypoplasia, high palatal arch, micropenis, and bilateral cryptorchidism. Laboratory examination revealed a diagnosis of multiple pituitary hormone deficiency. There was severe anterior pituitary hypoplasia, absent pituitary stalk and ectopic posterior pituitary on magnetic resonance imaging which suggested pituitary stalk interruption syndrome with no other midline structural abnormality. Molecular genetic analysis revealed a novel heterozygous splicing IVS11-2A>C(c.1957-2A>C) mutation detected in the GLI2 gene. His father and a six-year-old brother with the identical mutation also had unilateral postaxial polydactyly and mid-facial hypoplasia although there was no pituitary hormone deficiency. This novel heterozygous GLI2 mutation detected appears to present with an extremely variable clinical phenotype, even in related individuals with an identical mutation, suggesting incomplete penetrance of this GLI2 mutation.